Effects of κ-carrageenan on pullulan's rheological and texture properties as well as pullulan hard capsule performances. (15th June 2020) - Zhang, Yihui; Yang, Ning; Zhang, Yaqiong; Hou, Jingwen; Han, Huijie; Jin, Zhu; Shen, Yuanyuan; Guo, Shengrong
Highlights: The gelling temperature of 15 % PUL solution increased with the amount of κ-Ca added. KCl could facilitate the gelling of PUL and κ-Ca solutions. Addition of κ-Ca improved hardness, fracturability and adhesiveness of PUL gels. PUL capsules could be easily prepared by the aid of κ-Ca and KCl. The performances of PUL capsules could be adjusted by changing the amount of κ-Ca. Abstract: κ -Carrageenan ( κ -Ca) is often used to facilitate gelling of aqueous solutions of polysaccharides. However, studies on its effects on pullulan's rheological and texture properties and pullulan (PUL) hard capsule performances have rarely been reported. Herein, effects of κ -Ca on PUL solutions, hydrogels, films and hard capsules were investigated. It was found that the gelling temperature of 15 % (w/w) PUL solutions with 0.07 % KCl increased from 34 ℃ to 42 ℃ as the concentration of κ -Ca increased from 0.6 % to 1.2 %, and the gelling temperature rose from 25 ℃ to 37 ℃ by adding a small amount of KCl (0.07 %) for 15 % PUL solutions with 0.9 % κ -Ca. As the κ -Ca concentration increased, hardness, fracturability and adhesiveness rose for PUL gels and tensile stress increased for PUL films. PUL capsules could be easily prepared by the aid of κ -Ca, and performances of capsules could be adjusted by changing the amount of κ -Ca.